Online banking functionality and customer satisfaction: Empirical evidence from Northern Province Sri Lanka - Sutharsini, J.; Umakanth, N. (3rd Research Conference on Business Studies (RCBS) – 2020, 2020)
In today's advance technological era, every Financial Organization is agreed to cover their wide range of transactions through online or internet environments. Mostly Banks are spent a vast amount of money on impressing their customers and capturing new customers. The present study undertakes how online banking functionalities are determining customer satisfaction. To reach that purpose, the present study involved a quantitative approach concerning the design of surveys and the population— Northern Province is selected as a research sample. The researcher used specifically and the SPSS software version 20.0 had been used for the data analysis purposes. Based on this main study finding is that Convenience, Ease of use, as well as Fee & Charge, privacy, security and speed significantly contributed to customer satisfaction and also Accessibility, Content and website layout and design are not much contributed significantly in customer satisfaction. Furthermore, final some recommendations are given by the author. Iit also gives more support and direction to future work.
Keywords: Customer satisfaction; Functionalities; Northern Province; Online banking